Synthesis and Analysis of a Versatile DC-DC Converter Designed by Using Switched-Capacitor Techniques - Kei Eguchi; Sawai Pongswatd; Kitti Tirasesth; Hirofumi Sasaki; Takahiro Inoue (My University, 2009)
Aimed at mobile applications such as back-lighting applications, battery applications, and so on, a switched-capacitor (SC) DC-DC converter which offers a (N - s + 1)=(N - s) x mode ((N =2, 3,... ) and (s = 0, 1, 2,... )) as well as a step-down mode of operation is presented in this paper. Compared with conventional versatile converters, the proposed converter can realize high efficiency and flexibility of output voltages. The characteristics of the proposed converter are investigated by SPICE simulations and theoretical analyses. Concerning the power efficiency and the optimal duty factor, theoretical results are well in agreement with simulated results. Under conditions where input voltage Vin =3.7 V, output load RL = 30 , and output voltageVout = 3.3 5.3 V, the proposed converter can improve the power efficiency more than 20 % from that of the conventional circuit. Furthermore, the validity of circuit design is confirmed by using experimental circuit which is built with commercially available transistors.
Keywords: Switched capacitor; Duty cycle; Spice; Buck converter; Advanced DC-DC Converters